2020
DOI: 10.1371/journal.pone.0242126
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare workers’ knowledge, attitude and practices during the COVID-19 pandemic response in a tertiary care hospital of Nepal

Abstract: Background COVID-19 is an ongoing pandemic, for which appropriate infection prevention and control measures need to be adopted. Healthcare workers’ adherence to prevention and control measures is affected by their knowledge, attitudes, and practices (KAP) towards COVID-19. In this study, we assessed the KAP among healthcare workers towards the COVID-19 during the ongoing pandemic. Method A self-developed piloted KAP questionnaire was administered to the recruited healthcare workers involved in the COVID-19 r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
55
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 8 publications
17
55
1
Order By: Relevance
“…This finding aligns with a previous study among Chinese healthcare workers which reports 89.7% good practices towards COVID-19 (Zhang et al 2020). Importantly, the adherence to good practices is affected by the attitude of healthcare workers which is observed in the present study and is comparable to a study conducted in Nepal (Limbu et al 2020).…”
Section: Discussionsupporting
confidence: 89%
“…This finding aligns with a previous study among Chinese healthcare workers which reports 89.7% good practices towards COVID-19 (Zhang et al 2020). Importantly, the adherence to good practices is affected by the attitude of healthcare workers which is observed in the present study and is comparable to a study conducted in Nepal (Limbu et al 2020).…”
Section: Discussionsupporting
confidence: 89%
“…This moderate level of acceptance may be attributable to several reasons, e.g. inadequate knowledge among HCWs regarding COVID-19 [37,38], negative attitude towards the disease [37,39], and feelings of fear and anxiety during the COVID-19 pandemic [4043]. Also, concerns raised for COVID-19 vaccination are related with inadequate knowledge about such new vaccines regarding the long term side effects, effectiveness, efficacy etc.…”
Section: Discussionmentioning
confidence: 99%
“…Responses to reversed questions were reversed when assigning the points (Yes=0, No=1). The total knowledge score ranged from 0 to 19, with a higher score (16)(17)(18)(19) indicating a good knowledge of COVID-19. Similarly, the total attitude score ranged from 0 to 7.…”
Section: Data Collection Instrumentsmentioning
confidence: 99%
“…On the other hand, an Ethiopian study reported poor prevention practices toward COVID-19 among HCWs 15 while close to half of HCWs in Nepal were reported to have negative attitudes toward COVID-19. 16 Currently, it is not known how prepared frontline HCWs are regarding the COVID-19 outbreak response in Sierra Leone. Anecdotal evidence suggests that there might be a gap in the preparedness towards COVID-19 with regards to their knowledge, attitude and practice.…”
Section: Introductionmentioning
confidence: 99%